Experimental and numerical studies of press-braked S690 high strength steel channel section beams - Zhang, Lulu (2022)
The present paper describes an in-depth experimental and numerical investigation into the flexural responses and strengths of press-braked S690 high strength steel channel section beams bent about the minor principal axes in both the ‘u’ and ‘n’ orientations. The experimental study was performed on eight press-braked channel sections, and comprised twenty-four material flat and corner coupon tests, initial local geometric imperfection measurements, and twelve beam tests in the four-point bending configuration. This was followed by a complementary numerical modelling programme, where finite element models were firstly developed and validated against the test results and afterwards adopted for performing parametric studies to obtain an additional numerical data bank over a wide variety of cross-section geometric sizes. The acquired test and numerical data were then employed to evaluate the applicability of the Eurocode slenderness limits for welded and hot-rolled internal webs (in compression) and outstand flanges (in stress gradients) to their press-braked counterparts, revealing that the Eurocode slenderness limits can be safely extended to cover the classifications of plate elements and cross-sections of press-braked S690 high strength steel channel section beams. Evaluation of the accuracy of the cross-section flexural strengths predicted from various design codes established in Europe, North America and Australia/New Zealand was also made, based on the test and numerical data. The results of the quantitative evaluation generally revealed that (i) all the examined design codes lead to overall conservative and scattered predicted cross-section flexural strengths for press-braked S690 high strength steel channel section beams, and (ii) the European code results in more precise design flexural strengths for beams with relatively stocky channel sections, but less accurate strength predictions for beams with relatively slender channel sections, compared to the North American and Australian/New Zealand standards.